1997
DOI: 10.3181/00379727-215-44138
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Function in Mice with a Mutation at the Microphthalmia (mi) Locus

Abstract: Microphthalmic (mi/mi) mice are unpigmented, osteopetrotic, mast cell deficient, and exhibit diminished gastric acid secretion and natural killer cell activity. In order to assess the effect of this mutation on macrophage function, we studied superoxide (O2-) and nitric oxide (NO) production, superoxide dismutase (SOD) activity, phagocytic capacity, and tumor cell killing by peritoneal macrophages from mi/mi mice and normal (+/+) litter mates. Macrophages from mi/mi mice, upon activation with phorbol myristate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Monocytes and macrophages in the mouse express all 4 members of the MITF family ( MITF , TFEC , TFEB , and TFE3 ) [ 32 ], and these gene products have been implicated in regulating phagocyte-specific promoters associated with lysosomal hydrolases. All 4 members of the MITF family were differentially regulated in human myeloid cells from alternative promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes and macrophages in the mouse express all 4 members of the MITF family ( MITF , TFEC , TFEB , and TFE3 ) [ 32 ], and these gene products have been implicated in regulating phagocyte-specific promoters associated with lysosomal hydrolases. All 4 members of the MITF family were differentially regulated in human myeloid cells from alternative promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of Mitf gene in mice inhibits melanocytogenesis and retinal pigmented epithelium development, affects the number and function of mast cells, and inhibits late differentiation stage of osteoclasts (Steingrimsson et al 2004). Mutations of Mitf also causes dysfunctions of several hematopoietic cells (Rohan et al 1997; Roundy et al 1999; Stechschulte et al 1987; Thesingh and Scherft 1985) including macrophages, suggesting regulatory roles of Mitf in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…The authors regard hBDs to potentionally represent antimicrobial peptide-based therapeutic agents to deal with inXammatory reactions of the eye. Lu et al (2010) identiWed a domain in exon 1B1b to be responsible for cytoplasmic retention of microphthalmiaassociated transcription factor (Mitf), which has been shown to play regulatory roles in several hematopoietic cells (Rohan et al 1997;Roundy et al 1999;Stechschulte et al 1987;Thesingh and Scherft 1985) as well as in melanocytogenesis, retinal pigmented epithelium development and late diVerentiation stage of osteoclasts (Steingrimsson et al 2004). The authors suggested that the mechanism behind 1B1b-dependent nuclear entry possibly involves intramolecular NLS-masking (Bronisz et al 2006;Lu et al 2010).…”
Section: Epitheliummentioning
confidence: 98%